2020
DOI: 10.1021/acschemneuro.9b00459
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Metal-Ion-Induced Tau Oligomers to Lipid Surfaces Is Enhanced by GSK-3β-Mediated Phosphorylation

Abstract: While fibrillar deposits of hyperphosphorylated protein tau are a key hallmark of several neurodegenerative diseases such as Alzheimer’s disease, small oligomers have been speculated to be the key toxic aggregate species. Trivalent metal ions were shown to promote tau oligomer formation in vitro. However, little is known about potential intercellular spreading mechanisms or toxic modes of action of such oligomers. We investigated interactions of tau monomers and Fe3+/Al3+-induced oligomers with small unilamell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In mouse neuronal N2a cells expressing human 0N4R tau isoform, phosphorylated oligomeric tau is predominantly localized in the PM (Merezhko et al, 2018) and secreted across the PM through a vesicle-free pathway (Katsinelos et al, 2018). Moreover, tau phosphorylation by GSK3β does not affect 1N4R tau monomer-membrane binding but enhances tau oligomer-membrane binding in small unilamellar lipid vesicles which consist of 1-palmitoyl-2-oleoylphosphatidylcholine (POPC) or di-palmitoylphosphatidylcholine (DPPC) (Nuebling et al, 2020).…”
Section: The Role Of Phosphorylation In the Interaction Of Tau With Membranementioning
confidence: 99%
“…In mouse neuronal N2a cells expressing human 0N4R tau isoform, phosphorylated oligomeric tau is predominantly localized in the PM (Merezhko et al, 2018) and secreted across the PM through a vesicle-free pathway (Katsinelos et al, 2018). Moreover, tau phosphorylation by GSK3β does not affect 1N4R tau monomer-membrane binding but enhances tau oligomer-membrane binding in small unilamellar lipid vesicles which consist of 1-palmitoyl-2-oleoylphosphatidylcholine (POPC) or di-palmitoylphosphatidylcholine (DPPC) (Nuebling et al, 2020).…”
Section: The Role Of Phosphorylation In the Interaction Of Tau With Membranementioning
confidence: 99%
“…On the other hand, oligomeric Tau phosphorylated by GSK3b in vitro had a higher affinity for di-palmitoylphosphatidylcholine (DPPC) or 1-palmitoyl-2-oleoylphosphatidylcholine (POPC) unilamellar vesicles, whereas phosphorylation of monomeric 4R1N did not affect its lipid-binding affinity. 460 During apoptotic cell death phosphorylated aggregated Tau was enriched in the plasma membrane-containing PC12 cell line extracts. 461 Tau phosphorylation by Fyn kinase resulted in its recruitment and enrichment at the membrane in neuronal cells, 462 and oligomeric phosphorylated Tau was enriched at plasma membrane of human 4R0N-overexpressing murine neuronal N2a cell line.…”
Section: Is Heparin a Major Structural Component Of Tau Fibrils?mentioning
confidence: 97%
“…Ahmadi et al found, through electrochemical studies, that Fe 2+ showed a more significant effect in inducing tau aggregation than Fe 3+ , and that Fe 2+ also mediates tau interactions [94]. Fe 3+ can induce the pathological enhancement of hyperphosphorylated tau oligomer function, allowing phosphorylated tau to bind to membrane lipids at nanomolar protein concentrations, exacerbating disease progression [95]. Thus, the presence of iron may have a greater impact on tau pathology than previously thought.…”
Section: Iron Promotes Tau Phosphorylation Through Multiple Pathwaysmentioning
confidence: 99%